PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN PT. MARUTAKE MIYAMA INDONESIA - Adli Dzil Ikram; Syifa Pramudita Faddilla (Jurnal Pijar, 2023)
This study aims to determine the effect of work motivation on employee performance both in correlation, with a quantitative approach. This research was conducted at PT. Marutake Miyama Indonesia, which is located in the KIIC Karawang industrial area, Jl. Maligi VII Lot Q-4D east bayjambe, karawang district, west java province. With a population of 48 and the sample used is a non-probability sampling technique with SPSS calculations. Based on the research results, it can be concluded that there is a correlation between motivation and employee performance at PT. Marutake Miyama Indonesia is 0.578 which is quite strong, it can be said that the level of strength of the relationship between work motivation and employee performance has a fairly strong relationship. the coefficient of determination is 33.4%, which means that the work motivation variable contributes 33.4% to the employee performance variable. While the remaining 67.6% is caused by other factors not examined by the author. It can be concluded that work motivation contributes 33.4% to employee performance variables at PT Marutake Miyama Indonesia